STUDI KASUS PEMENUHAN KEBUTUHAN NUTRISI PADA PASIEN PPOK DI RUMAH SAKIT TINGKAT II PUTRI HIJAU MEDAN TAHUN 2017 - Lermiana Purba; Deni Susyanti; Lilis Savanna Siahaan (Jurnal Riset Hesti Medan, 2017)
Background of  Chronic Pulmonary Obstruction Disease (COPD) is identified by productive coughing, dyspnea, and obstruction in the respiratory tract. It is the combination of emphysema, chronic bronchiolitis, and asthma. One of the symptom of COPD is the decrease in bodyweight. The research used descriptive method with 2 COPD patients at Putri Hijau Level II Hospital Medan. The result of the analysis on the 2 patients showed that their need for nutrition was fulfilled but in different time, the need for nutrition in patient 1 was fulfilled in the 2nd day while in patient 2 it was fulfilled in the 3nd day due to the difference in their age. The conclusion was that the need for nutrition in COPD patients was different because of the difference in age. It is recommended that COPD patients always pay attention to the program in fulfilling their need for nutrition.Keywords: Nutrition, Chronic Obstruction Pulmonary Desease, Chronic